Pre-hospital risk factors for inpatient death from severe febrile illness in Malian children. - Merlin L Willcox (Public Library of Science (PLoS), 2014)
Background Inpatient case fatality from severe malaria remains high in much of sub-Saharan Africa. The majority of these deaths occur within 24 hours of admission, suggesting that pre-hospital management may have an impact on the risk of case fatality. Methods Prospective cohort study, including questionnaire about pre-hospital treatment, of all 437 patients admitted with severe febrile illness (presumed to be severe malaria) to the paediatric ward in Sikasso Regional Hospital, Mali, in a two-month period. Findings The case fatality rate was 17.4%. Coma, hypoglycaemia and respiratory distress at admission were associated with significantly higher mortality. In multiple logistic regression models and in a survival analysis to examine pre-admission risk factors for case fatality, the only consistent and significant risk factor was sex. Girls were twice as likely to die as boys (AOR 2.00, 95% CI 1.08-3.70). There was a wide variety of pre-hospital treatments used, both modern and traditional. None had a consistent impact on the risk of death across different analyses. Reported use of traditional treatments was not associated with post-admission outcome. Interpretation Aside from well-recognised markers of severity, the main risk factor for death in this study was female sex, but this study cannot determine the reason why. Differences in pre-hospital treatments were not associated with case fatality.